Parameter Hak Monopoli Badan Usaha Milik Negara dalam Perspektif Persaingan Usaha di Indonesia - Lelly Rosa Sidabutar; Luna Dezena Ticoalu; Relys Sandi Ariani; Mochammad Abizar Yusro (Fakultas Hukum, Universitas Internasional Batam, 2021)
State-owned enterprises (BUMN) certainly play a very important role as actors in economic activities based on economic democracy in accordance with the Pancasila economy, whose activities must pay attention to the balance between the interests of business actors and the public interest. However, granting monopoly rights to BUMN has been further regulated, so that in the future it can create fair business competition in market competition in Indonesia. The exclusion of monopoly rights is only one sentence in article 51, so that it still creates legal ambiguity for the implementation of monopolistic practices granted to BUMN. The contribution of this research aims to encourage further regulation regarding monopoly by BUMN. In addition, it is also used as academic library material so that it can be used as a reference and material for other academic studies. This research uses a normative juridical study with a statutory approach and a conceptual approach. Thus, this research results in a study of BUMN monopoly rights from the perspective of business competition in Indonesia.